Penerapan Metode Best First Search Pada Permainan Tic Tac Toe - Hutahaean, Harvei Desmon (LPPM UNIKA Santo Thomas Medan, 2017)
Search is the process of finding solutions in a problem until a solution or goal is found, or a movement in the state-space to search for trajectories from initial-state to goal-state. In a TIC TAC Toe game the process of finding a space situation is not enough to automate problem-solving behavior, in each of these situations there are only a limited number of choices that a player can make. The problems that will be faced can be solved by searching from the choices available, supported by the usual way of resolving. Best First Search works by searching for a directed graph which each node represents a point in a problem space.